(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
This research is motivated by problems that often occur in the environment that women who look attractive tend to get more benefits. Many people say that someone who looks attractive was easier to get a job and often gets special treatment from the people around. This research aims to find out how the issue of beauty privilege uses Roland Barthes’ semiotic theory in the movie of "Sierra Burgess is a Loser". This reseacrh used a qualitative descriptive method and this research approach used Roland Barthes’ semiotics. The data in this research were taken from the movie of "Sierra Burgess is a Loser" directed by Ian Samuels. The data collection technique in this study is watching the movie, dividing the movie into several scenes based on the research problems, then analyzing the movie using Roland Barthes’ semiotic analysis, and drawing conclusions from the results of the analysis. The results of this research state that beauty can’t be measured by a person’s appearance, while the problem of beauty privilege in this movie was someone who looks attractive got more benefit from various aspects.